Differences in H3K4me3 and chromatin accessibility contribute to altered T‐cell receptor signaling in neonatal naïve CD4 T cells. Issue 7 (20th June 2022) - Bermick, Jennifer R; Issuree, Priya; denDekker, Aaron; Gallagher, Katherine A; Santillan, Donna; Kunkel, Steven; Lukacs, Nicholas; Schaller, Matthew
Abstract: Neonatal CD4 + T cells have reduced or delayed T‐cell receptor (TCR) signaling responses compared with adult cells, but the mechanisms underlying this are poorly understood. This study tested the hypothesis that human neonatal naïve CD4 + TCR signaling and activation deficits are related to differences in H3K4me3 patterning and chromatin accessibility. Following initiation of TCR signaling using anti‐CD3/anti‐CD28 beads, adult naïve CD4 + T cells demonstrated increased CD69, phospho‐CD3ε and interleukin (IL)‐2, tumor necrosis factor‐α (TNF‐α), interferon‐γ and IL‐17A compared with neonatal cells. By contrast, following TCR‐independent activation using phorbol myristate acetate (PMA)/ionomycin, neonatal cells demonstrated increased expression of CD69, IL‐2 and TNF‐α and equivalent phospho‐ERK compared with adult cells. H3K4me3 chromatin immunoprecipitation‐sequencing (ChIP‐seq) and assay for transposase‐accessible chromatin with high‐throughput sequencing (ATAC‐seq) were performed on separate cohorts of naïve CD4 + T cells from term neonates and adults, and RNA‐seq data from neonatal and adult naïve CD4 + T cells were obtained from the Blueprint Consortium. Adult cells demonstrated overall increased chromatin accessibility and a higher proportion of H3K4me3 sites associated with open chromatin and active gene transcription compared with neonatal cells. Adult cells demonstrated increased mRNA expression of the TCR‐associated genes FYN, ITK, CD4, LCK and LAT, which was associated with increased H3K4me3 at the FYN and ITK gene loci and increased chromatin accessibility at the CD4, LCK and LAT loci. These findings indicate that neonatal TCR‐dependent defects in activation are epigenetically regulated and provide a potentially targetable mechanism to enhance neonatal CD4 + T‐cell responses. Abstract : This study found that human neonatal naïve CD4 + T cells have a T‐cell receptor–dependent defect in activation. This activation defect is associated with decreased mRNA expression of several T‐cell receptor signaling–associated genes in neonatal cells, with decreased H3K4me3 enrichment and/or decreased chromatin accessibility at these gene loci. This suggests that the neonatal defect in CD4 + T‐cell receptor signaling is epigenetically regulated.